Determinants of COVID-19 severity and mortality in children: A retrospective and multicenter cohort study in Medan, Indonesia - Airlangga, Eka; Wahyuni, Arlinda S.; Siregar, Jelita; Malisie, Ririe F.; Lubis, Bugis M.; Adisasmito, Wiku B.; Zarlis, Muhammad; Pasaribu, Ayodhia P. (Narra Sains Indonesia, 2024)
This study investigated indicators of the severity and mortality of COVID-19 in children in Medan, Sumatera Utara Province, Indonesia. The aim of this study was to identify determinants of severity and outcome of children with COVID-19 as the lesson learned from the COVID-19 pandemic, particularly the limited health facilities in Indonesia. This retrospective cohort study was conducted in 2020, 2021, and 2022 at multiple centers. Inpatient and outpatient children confirmed to be SARS-CoV-2 positive were randomly recruited in the selected hospitals. Baseline data (demographic, clinical, laboratory and radiological data) were collected, and outcomes were classified as recovered/deceased (for the inpatient group) or returned to the hospital (for the outpatient group). Severity status was identified based on the Indonesia COVID-19 guidelines. The laboratory data were categorized according to international standards, and data were analyzed using univariate analyzes followed by multivariate logistic regression. A total of 303 inpatient and 114 outpatient children were included in the analysis. Out of the total inpatient cases, 11 patients died with 3.6 mortality rate. Our final multivariate indicated that the presence of shortness of breath (SOB), anemia, and abnormal C-reactive protein (CRP) levels were significantly associated with the severity or the presence of emergency signs, while the presence of SOB and comorbidities were significantly associated with mortality in inpatient children with COVID-19. The presence of fever, cough, SOB, muscle ache and diarrhea were the reasons why the children were returned to the hospital from self-isolation at home among outpatient COVID-19 cases; however, the cough was the only significant factor in the final multivariate mode. This study highlights important determinants of COVID-19 severity and mortality in children, which should be considered during clinical decision-making in low-resource settings of healthcare centers in Indonesia.